Pengaruh Kebijakan Deviden, Struktur Modal, Ukuran Perusahaan, dan Kepemilikan Institusional terhadap Nilai Perusahaan pada Sektor Consumer Good yang Listing di Bursa Efek Indonesia (BEI) Periode 2012-2016 - DITA PUTRI PRADANI, KARINA; SENO AJI, TONY (Jurnal Ilmu Manajemen (JIM), 2018)
The purpose of this research is to determine the effect of dividend policy, capital structure, firm size, and institutional ownership toward firm value in the consumer good sector listing in Indonesia Stock Exchange (IDX) period 2012-2016. This study uses quantitative research type, with secondary data in the form of companys financial statements obtained from the official website of Indonesia Stock Exchange (IDX). The analytical method used is multiple regression analysis with the help of SPSS 24 software analysis tool. The results of research showed that dividend policy and institutional ownership have an effect on firm value, while firm size and capital structure have no effect to firm value. This imply that dividend policy and institutional ownership have an effect on firm value because investors prefer dividends over capital gain. Whereas for institutional ownership, individual investors feel that firm give priority to institutional investors to the detriment of individual investor. Capital structure does not effect the value of the company because debt increases the risk of bankruptcy for the company. As for the firm size, investor will not judge its worth based on all aspects of the company such as the level of sales, corporate financial statements, and reputation company.